2021
DOI: 10.1177/14759217211060780
|View full text |Cite
|
Sign up to set email alerts
|

Probability of detection, localization, and sizing: The evolution of reliability metrics in Structural Health Monitoring

Abstract: The successful implementation of Structural Health Monitoring (SHM) systems is confined to the capability of evaluating their performance, reliability, and durability. Although there are many SHM techniques capable of detecting, locating and quantifying damage in several types of structures, their certification process is still limited. Despite the effort of academia and industry in defining methodologies for the performance assessment of such systems in recent years, many challenges remain to be solved. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 147 publications
(269 reference statements)
0
26
0
Order By: Relevance
“…In this case, the hypothesis of statistical independence of the observations does not hold anymore, making it impossible to apply the standard linear regression model used for POD in NDE studies. 21 The LaD method avoids the issue of dealing with repeated measurements by considering only one observation among the time series of data. Similar to the standard method proposed in the MIL-HKBK-1823A, 12 detection is positive if a certain measurement is above a certain threshold.…”
Section: Pod For Shm: Lad Methodsmentioning
confidence: 99%
“…In this case, the hypothesis of statistical independence of the observations does not hold anymore, making it impossible to apply the standard linear regression model used for POD in NDE studies. 21 The LaD method avoids the issue of dealing with repeated measurements by considering only one observation among the time series of data. Similar to the standard method proposed in the MIL-HKBK-1823A, 12 detection is positive if a certain measurement is above a certain threshold.…”
Section: Pod For Shm: Lad Methodsmentioning
confidence: 99%
“…Actions related to the first category aim to provide insight about the presence, location, type as well as extent of the damage. 14 Prognostics in turn perform predictions regarding the remaining useful life of the monitored structure. 15 The DT concept is a promising approach for SHM that combines sensor data with a numerical model, for example, FE model, in order to interpret the underlying phenomena of damage evolution in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a detailed bibliography on the topic was presented by Falcetelli et al [ 21 ], who focused on the main challenges and barriers that currently prevent the development of proper reliability metrics for SHM. Starting from the analysis of the main differences with respect to POD methodologies for NDE, the authors found that a higher level of statistical expertise is required to achieve POD curves for SHM systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some simplified experiments have been carried out on extending the reliability concept to complex structures, such as aeronautical composite coupons and subsystems [ 22 ]. Falcetelli et al [ 21 ] also oriented the discussion beyond classical POD curves, approaching new metrics such as probability of localization (POL) and probability of sizing (POS) curves. Actually, this aspect reflects the diagnosis paradigm of SHM, which aims to detect, localize and assess the size of a damage.…”
Section: Introductionmentioning
confidence: 99%